2018
DOI: 10.1016/j.ypmed.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Talking about tobacco on Twitter is associated with tobacco product use

Abstract: Tobacco-related content appears on social media in the form of advertising and messages by individuals. However, little is known about associations between posting social media messages and tobacco product use among adolescents and young adults. Self-reports of tobacco product use were obtained from the Children's Health Study of young adults in Southern California. Among the 1486 respondents in the most recent wave of the cohort (2016-2017), 284 provided tobacco product use data and their Twitter user names t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Categorising Instagram user profiles is key to describing the nature of engagement associated with posts related to KandyPens. Previous evidence suggests that engagement with tobacco-related social media information is associated with tobacco use21 22 and/or low support for e-cigarette regulations 23 . Average Instagram users and vape enthusiasts/advocates alike can extend conversations by demonstrating novel open-system pod mod use to their followers 24.…”
Section: Discussionmentioning
confidence: 99%
“…Categorising Instagram user profiles is key to describing the nature of engagement associated with posts related to KandyPens. Previous evidence suggests that engagement with tobacco-related social media information is associated with tobacco use21 22 and/or low support for e-cigarette regulations 23 . Average Instagram users and vape enthusiasts/advocates alike can extend conversations by demonstrating novel open-system pod mod use to their followers 24.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have shown associations between self-reported behavior and tweet content. In particular, Unger et al [43] showed that posting positive tweets about tobacco had a significant association with tobacco use within the past month.…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of tobacco communication have been linked to tobacco use in youth 10,11,[13][14][15] , suggesting the need for antitobacco campaigns aimed at reducing tobacco initiation and continued use in youth. Prior work emphasizes a need to develop broad-based initiatives that reduce youth exposure to positive tobacco messages 26,27 .…”
Section: Discussionmentioning
confidence: 99%